CLINICAL FEATURES OF COMMON INFECTIONS IN CHILDREN UNDER 14 YEARS OF AGE WITH HIV (Multidisciplinary Journal of Science and Technology, 2026)
Renal impairment against the background of HIV infection (HIV-associated nephropathy) is a major non-infectious factor exacerbating disease outcomes. This study aims to optimize the early diagnosis of renal pathologies and antiretroviral therapy (ART) regimens in HIV-infected patients. Observations demonstrated that subclinical screening using cystatin-C and microalbuminuria, combined with a transition to low-nephrotoxicity ART regimens, significantly reduces the risk of developing renal failure. The conceptual findings serve as a crucial clinical platform for refining regional nephrological and infection control protocols and improving patients' quality of life.